Are shed hair genomes the most effective noninvasive resource for estimating relationships in the wild?. Issue 11 (18th May 2020) - Khan, Anubhab; Patel, Kaushalkumar; Bhattacharjee, Subhadeep; Sharma, Sudarshan; Chugani, Anup N.; Sivaraman, Karthikeyan; Hosawad, Vinayak; Sahu, Yogesh Kumar; Reddy, Goddilla V.; Ramakrishnan, Uma
Abstract: Knowledge of relationships in wild populations is critical for better understanding mating systems and inbreeding scenarios to inform conservation strategies for endangered species. To delineate pedigrees in wild populations, study genetic connectivity, study genotype‐phenotype associations, trace individuals, or track wildlife trade, many identified individuals need to be genotyped at thousands of loci, mostly from noninvasive samples. This requires us to (a) identify the most common noninvasive sample available from identified individuals, (b) assess the ability to acquire genome‐wide data from such samples, and (c) evaluate the quality of such genome‐wide data, and its ability to reconstruct relationships between animals within a population. We followed identified individuals from a wild endangered tiger population and found that shed hair samples were the most common compared to scat samples, opportunistically found carcasses, and opportunistic invasive samples. We extracted DNA from these samples, prepared whole genome sequencing libraries, and sequenced genomes from these. Whole genome sequencing methods resulted in between 25%–98% of the genome sequenced for five such samples. Exploratory population genetic analyses revealed that these data were free of holistic biases and could recover expected population structure and relatedness. Mitochondrial genomes recovered matrilineages in accordance with long‐term monitoring data. Even with just five samples, we were able to uncover the matrilineage for three individuals with unknown ancestry. In summary, we demonstrated that noninvasive shed hair samples yield adequate quality and quantity of DNA in conjunction with sensitive library preparation methods, and provide reliable data from hundreds of thousands of SNPs across the genome. This makes shed hair an ideal noninvasive resource for studying individual‐based genetics of elusive endangered species in the wild. Abstract : Recovering relationships and relatedness among individuals is important to study wild populations. However, noninvasive samples from specific individuals are difficult to obtain and difficult to use for whole genome sequencing. Here, we show that shed hair collected by following the individuals in a population is the best source of identified noninvasive genetic material and also that whole genome sequences can be recovered reliably from shed hair.